2016
DOI: 10.1007/978-1-4939-3530-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Protein-Protein Associations at the Nuclear Envelope with BioID

Abstract: Summary The nuclear envelope (NE) is a critical cellular structure whose constituents and roles in a myriad of cellular processes seem ever expanding. To determine the underlying mechanisms by which these NE constituents participate in various cellular events, it is necessary to understand the nature of their protein-protein associations. BioID (proximity-dependent biotin identification) is a recently established method to generate a history of protein-protein association as they occur over time in living cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…We have modified the promiscuous biotin ligase tagging system (85)(86)(87)(88) to analyze the protein interaction networks of the G12D, WT, S17N, and C185S/G12D K-Ras proteins. As shown, our chimeric BirA*Ras proteins were expressed as expected, localized as predicted, and their localization patterns matched the patterns of the proteins they biotinylated (Figures 1-4).…”
Section: Discussionmentioning
confidence: 99%
“…We have modified the promiscuous biotin ligase tagging system (85)(86)(87)(88) to analyze the protein interaction networks of the G12D, WT, S17N, and C185S/G12D K-Ras proteins. As shown, our chimeric BirA*Ras proteins were expressed as expected, localized as predicted, and their localization patterns matched the patterns of the proteins they biotinylated (Figures 1-4).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the top cellular component terms included nuclear periphery (GO:0034399), nuclear lamina (GO:0005652), and nuclear matrix (GO:0016363) ( Figure 2C). To further examine if our data was consistent with previous studies we benchmarked our data on four published studies of nuclear envelope interactomes [21][22][23]27,28,36,37] : ( 1 ) Bar et al combined a novel antibody based proximity labeling strategy and a meta-analysis of many lamin A and B interactome studies that included methods such as BioID, yeast two hybrid, and co-immunoprecipitation. .…”
Section: Analysis Of the Lap2β Interactome Using Bioidmentioning
confidence: 84%
“…Previous studies have identified proteins enriched at the nuclear lamina (the "laminome") through multiple methods, including BioID [21][22][23][24][25] . Here we use BioID with BioSITe (BioID coupled with biotinylation site enrichment and analysis) to measure protein-protein interactions of the INM protein Lap2β (Figure 2) in MEFs and integrate these with the previous laminome findings to generate an enhanced INM/lamina proteome map [21][22][23]27,28,36,37] . Not surprisingly, the majority of Lap2β protein-protein interactions uncovered in this study were previously identified as part of the laminome.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations